2004
DOI: 10.1021/bi0494121
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillation of Carrier Protein Albebetin and Its Biologically Active Constructs. Multiple Oligomeric Intermediates and Pathways

Abstract: We showed that the genetically engineered carrier-protein albebetin and its biologically active constructs with interferon-alpha(2) octapeptide LKEKKYSP or differentiation factor hexapeptide TGENHR are inherently highly amyloidogenic at physiological pH. The kinetics of fibrillation were monitored by thioflavine-T (ThT) binding and the morphological changes by atomic force microscopy. Fibrillation proceeds via multiple pathways and includes a hierarchy of amyloid structures ranging from oligomers to protofilam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 35 publications
6
47
1
Order By: Relevance
“…2 shows that the rings exhibit a clearly segmented structure, and the molecular dimensions of the segments are similar to the parameters of individual oligomers present in solution, which suggests that the rings can be formed from round-shaped oligomers. A similar morphology was observed in the amyloid rings of the de novo designed protein albebetin, which also demonstrate a well defined segmentation and are assembled from oligomers (31).…”
Section: Discussionsupporting
confidence: 64%
“…2 shows that the rings exhibit a clearly segmented structure, and the molecular dimensions of the segments are similar to the parameters of individual oligomers present in solution, which suggests that the rings can be formed from round-shaped oligomers. A similar morphology was observed in the amyloid rings of the de novo designed protein albebetin, which also demonstrate a well defined segmentation and are assembled from oligomers (31).…”
Section: Discussionsupporting
confidence: 64%
“…The compactness of this molecule is achieved due to short loops connecting the secondary structure elements. In our previous studies we have shown that albebetin readily assembles into a variety of amyloid structures during its incubation under physiological conditions [21]. Here we examine the cytotoxic properties of main amyloid species of albebetin relating their structural properties with exerted cytotoxicity.…”
Section: Introductionmentioning
confidence: 91%
“…8). The cytotoxicity of the soluble, oligomeric forms is dependent on the type of oligomeric species [153][154][155][156][157][158][159], and existence of both on-and off-pathway oligomers has been proposed [20,60,150,153,160]. Hydrophobic probes such as 8-anilino-1-naphthalenesulfonic acid and the molecular rotor 9-dicyanovinyl-julolidine have been shown to respond to earlier species such as TTR oligomeric species [60].…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%